Preparation and characterization of Pd/porous Ta/Ta composite membrane - LI Guangzhong; WANG Hao; LI Yaning; HUANG Yuanping (Fenmo yejin jishu, 2024)
The porous Ta membrane was prepared on the surface of Ta foils by spraying and sintering. Subsequently, the Pd/porousTa/Ta composite membrane was prepared by electroless Pd plating processes using the porous Ta/Ta as the composite substrate. The effect of sintering temperature on the morphology of porous tantalum films was studied, and the growth behavior of Pd films was analyzed. In the results, the sintering temperature has a significant impact on the structure of porous Ta membrane. The porous Ta membrane with the well-developed sintering neck can be obtained by sintering at 1700 ℃ for 2 h. The electroless plating time has a significant effect on the Pd membrane on the surface of porous Ta membrane. Moreover, due to the complex surface structure of porous Ta membrane, it is difficult to obtain the uniform and dense Pd membrane on the surface of porous Ta membrane.